Assessment of local water distribution infrastructure management and maintenance challenges - Mothetho, Motlatsi (Department of Civil Engineering, 2019)
Central to the South African government’s vision of providing services to all is on-going maintenance of public infrastructure. Since 1994 the government focused on addressing backlogs in the provision of water services through new infrastructure investment; however it failed to make sufficient investment in the maintenance and renewal of this infrastructure (SAICE, 2006). Older infrastructure is not being renewed or refurbished as required and planned preventative maintenance on new infrastructure is inadequate (SAICE, 2006). This has been generally attributed to poor management strategies that are exacerbated by lack of skills in water services utilities and low levels of funding provisions (Mescht & Jaarsveld, 2012; FFC, 2013). The continuing poor maintenance of water distribution networks has contributed to high leakage rates in South Africa (FFC, 2013; DBSA, 2012). To address challenges of maintenance of water distribution infrastructure a regulatory framework to guide municipalities is critical. The government approved the National Infrastructure Management Strategy (NIMS) in 2006 to support simultaneous infrastructure investment and maintenance (CIDB, 2008). One of the key thrusts of the strategy is the strengthening of the regulatory framework that governs planning and budgeting for maintenance. The literature survey of this study found that initiatives associated with the NIMS were very slow in gaining traction. The study reviews water services infrastructure management frameworks that are based on present legislative instruments and standards for two study areas; City of Capetown and City of Johannesburg. Challenges associated with effective management of water distribution infrastructure are assessed based on established infrastructure management policies, strategies and asset management plans for each entity. For each study area leakage control strategies are the key maintenance strategy outputs associated with the implementation of the management frameworks; therefore the study reviewed sector plans and annual reports to assess challenges associated with carrying out effective maintenance. The findings of the study show a correlation between the adoption of maintenance management strategies and the improvement of the performance of water distribution networks for both Cape Town and Johannesburg. The strategies are driven at the highest level of decision making in the municipalities as budgeting requirements are supported by the Integrated Development Plans of each study area. The maintenance allocations however remain below the international benchmark to enable the municipal entities to carry out satisfactory maintenance of their distribution infrastructure.